2020
DOI: 10.1038/s41598-020-59423-3
|View full text |Cite
|
Sign up to set email alerts
|

Lasing with Topological Weyl Semimetal

Abstract: Lasing behavior of optically active planar topological Weyl semimetal (TWS) is investigated in view of Kerr and Faraday rotations. Robust topological character of TWS is revealed by the presence of Weyl nodes and relevant surface conductivities. We focus our attention on the surfaces where no fermi arcs are formed, and thus Maxwell equations contain topological terms. We explicitly demonstrate that two distinct lasing modes arise because of the presence of effective refractive indices which lead to the birefri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…1A). Interestingly, rs55705857 is not associated with the risk of IDH-wild type (IDH-WT) glioma or other cancers, including IDH-mutant acute myeloid leukemia (6)(7)(8).…”
mentioning
confidence: 99%
“…1A). Interestingly, rs55705857 is not associated with the risk of IDH-wild type (IDH-WT) glioma or other cancers, including IDH-mutant acute myeloid leukemia (6)(7)(8).…”
mentioning
confidence: 99%
“…One such example is the topological magnetoelectric effect. The topological magneto-electric effect is a phenomenon when an electric field produces a magnetic field in the same direction (parallel to itself) as odd multiples of the fine structure constant, α = e 2 /4πε 0 hc [25]. Certain types of Weyl semimetals can exhibit strong CD, which can lead to a rotation of the polarization of an incident electromagnetic wave.…”
Section: Maxwell's Equations For a Twsmentioning
confidence: 99%
“…Of course, this tutorial review cannot cover all the reported optical phenomena and applications of Weyl semimetals. Here we list some examples of other phenomena and applications not covered in this review: gyrotropic magnetic effect [249], photoinduced anomalous Hall effect [250], nonlinear magneto-optical effects [185], topological frequency conversion [251], emergent electromagnetic induction [252,253], tunable perfect absorption [254], unidirectional bound states in the continuum [255], transverse Kerker effect [256], and topological lasers [257].…”
Section: Other Effectsmentioning
confidence: 99%